White collar crime, consumers and victimization - Croall, Hazel (2008)
Consumers have long been recognized as one of the major groups of victims of white collar and corporate crime, although many of the activities which harm them are not widely regarded as 'crime'. They tend to attract less publicity, and have been subject to less academic research, particularly in comparison with major financial frauds or cases involving mass harms. Moreover, there has been a tendency to view consumers as a relatively undifferentiated group, all of whom are likely to be victimized. This article identifies a wide range of crimes which affect consumers and explores some of the characteristics of victims and offenders, arguing that while all consumers are at risk, the impact of consumer crime, like other forms of crime, reflects wider patterns of structural inequality and falls most severely on the most disadvantaged.